Rashoul the cave troll - Blade, Adam; Tucker, Ezra (New York : Scholastic Inc., 2011)
Tom must face Rashouk the Cave Troll, a terrifying beast who lurks in the darkness and strikes fear into the people of Avantia. To save the land from destruction, Tom must confront Rashouk and stop Malvel$1 (Bs evil plot.s
Keywords: Fantasy fiction; Monsters -- Juvenile fiction